WWW-based Boolean function minimization - Tomaszewski, Sebastian P.; Celik, Ilgaz U.; Antoniou, George E. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper a Boolean minimization algorithm is considered and implemented as an applet in Java. The application is based on the Quine-McCluskey simplification technique with some modifications. The given application can be accessed on line since it is posted on the World Wide Web (WWW), with up to four variables, at the URL http://www.csam.montclair.edu/~antoniou/bs.
Keywords: digital logic; logic design; Boolean functions; Boolean minimization; Quine-McCluskey method